Hot Rocks Survey. IV. Emission from LTT 3780 b Is Consistent with a Bare Rock - Allen, Natalie H.; Espinoza, Néstor; Diamond-Lowe, Hannah; Mendonça, João M.; Demory, Brice Olivier; Gressier, Amélie; Ih, Jegug; Fortune, Mark; August, Prune C.; Holmberg, Måns; Meier Valdés, Erik; Zgraggen, Merlin; et al. (Astronomical Journal, 2025)
It is an open question whether small planets around M dwarfs are able to maintain atmospheres. The Hot Rocks Survey aims to address this question by observing nine rocky exoplanets orbiting M dwarfs with MIRI emission photometry to constrain the onset of atmospheres. In this paper, we present two MIRI F1500W (15 μm) eclipses of LTT 3780 b, an ultrashort-period super-Earth (P = 0.768 days, R = 1.325 R⊕, M = 2.46 M⊕) that receives 111× Earth’s instellation, the highest in the survey. We find a combined eclipse depth of 312 ± 38 ppm, which is consistent between different data reduction and analysis assumptions, bolstering our confidence in the eclipse detection. This eclipse depth is consistent with the thermal emission from a bare rock surface, with a dayside temperature of T day = 114 3 − 99 + 104 K, 98% ± 9% of the maximum temperature predicted for a zero-albedo, zero heat redistribution blackbody. We are able to confidently rule out CO2-based atmospheres down to a 0.01 bar surface pressure to greater than 3σ (ruling out an approximately Mars-like atmosphere). We are unable to rule out a pure H2O 1 bar atmosphere, though we argue that this composition is unlikely on such a highly irradiated planet, nor O2 atmospheres due to the lack of features in the bandpass, though we can put constraints on CO2-mixture atmospheres. As a potential bare rock, we consider a variety of surface composition models, but are unable to distinguish between them. However, LTT 3780 b is an excellent target for follow-up JWST observations to determine its surface composition and rule out additional atmospheric compositions.